The Dynamics of Education Funding: A Madrasah Ibtidaiyah Perspective (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study examines the management of education financing, focusing on the primary funding sources and the challenges associated with their management. Design/Methodology/Approach: A qualitative approach was employed, using in-depth interviews with the school principal to explore funding sources, challenges, and the practices implemented to manage these resources effectively. Research findings: The research revealed that the primary funding sources are government allocations SOS (School Operational Support) and RSOS (Regional School Operational Support), parental contributions (tuition fees and infaq), and community donations. Challenges include dependency on unstable external funding, irregular disbursement of government funds, economic constraints affecting parental contributions, and the unpredictability of community donations. These challenges highlight the need for diversifying funding sources and enhancing transparency in financial management. Theoretical contribution/Originality: This study underscores the critical need for diversified and transparent financial management in educational institutions. It provides insights into managing dependency on external funding and improving sustainability in educational financing, contributing to the broader discourse on funding models in primary education. Practitioner/Policy Implication: The findings suggest policy recommendations for improving the reliability of government fund disbursement, developing support programs for economically disadvantaged parents, and establishing community partnerships to secure consistent funding.